Avaliação da força muscular respiratória e função pulmonar de pacientes submetidos à cirurgia cardíaca - Ferreira, Priscila Ribeiro (2018)
The present study aimed to evaluate the respiratory muscle strength and lung function in patients undergoing cardiac surgery. This research was performed at the Coronary Intensive Care Unit (UCO) of the Hospital de Clínicas de Uberlândia. We evaluated 14 patients submitted to elective cardiac surgery. We measured the values of inspiratory (Pimáx) and expiratory (Pemáx) respiratory muscle strength, as well as the values of Forced Vital Capacity), Expiratory Volume in the first second (FEV1), index of relation between them (FEV1 / FVC or Tiffenaud Index) and Expiratory Flow Peak in liters per second (PEF). There was a reduction in the values of respiratory muscle strength, when compared to the pre and postoperative periods, both in Pimáx: pre 66,5 (50 - 91,5), post 46,50 (40 - 62,50) p = 0,019 , and in Pemáx: pre 105, 5 (94 - 120) and postoperative: 80 (68.75 - 91.0), (p = 0.004) as well as in tidal volume values (pre 438.50 (351 - 550), post 307 (231.75 - 443.5), p = 0.043. However, there was no significant difference in minute volume values pre 6,00 (5,0 - 8,5) and post 4,5 (4,0 - 9,25), p = 0,237. The spirometric values of pre FEV1: 2.6 ± 0.49, post: 2.16 ± 0.66, and Slow Vital Capacity, pre: 2.6 ± 0.49 and post 2.16 ± 0.66 were post-surgery decreased, (FEV1 / FVC) pre: 0.78 ± 0.065 and post: 0.78 ± 0.65 p = 1,000, and the pre PEF: 5.04 (p = 0.0035 and p = 0.004, respectively). ± 1.70 and post: 4.50 ± 1.91, p = 0.442, showed no statistical difference. Conclusion: There was a worsening of lung function, as well as reduction of respiratory muscle strength in patients submitted to cardiac surgery.